1978
DOI: 10.1104/pp.61.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Induction of “Pore” Formation in Plant Cell Membranes by Toluene

Abstract: Treatment with aqueous toluene-ethanol has been shown to induce "pore" formation in plant cell membranes. The evidence i as folows: Althoug the phenomenon of pore induction is qultatively simlar to that in microorganisms, the pores induced appear to be smaler. It is proposed that induced leakage could be the bas for the development of simple and rapid methods for plant biochemial studies.Biochemical studies of cells provided with hard outer walls are hindered by the technical difficulties involved in homogeniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 16 publications
0
15
1
Order By: Relevance
“…This can be analogous to the change in shape and size caused by the shrinkage and therefore, the increase in FD that certain biological materials undergo when dried (Chanona et al, 2003;Alamilla-Beltrán et al, 2005). It has been reported that one of the mechanisms of the permeabilization process is the formation of micropores or microchannels through the cell wall that allow the flow of metabolites (Lerner et al, 1978;Brodelius, 1988). The quantity of micropores and their temporality are functions of the type, concentration and contact time of the permeabilizing agent.…”
Section: Resultsmentioning
confidence: 99%
“…This can be analogous to the change in shape and size caused by the shrinkage and therefore, the increase in FD that certain biological materials undergo when dried (Chanona et al, 2003;Alamilla-Beltrán et al, 2005). It has been reported that one of the mechanisms of the permeabilization process is the formation of micropores or microchannels through the cell wall that allow the flow of metabolites (Lerner et al, 1978;Brodelius, 1988). The quantity of micropores and their temporality are functions of the type, concentration and contact time of the permeabilizing agent.…”
Section: Resultsmentioning
confidence: 99%
“…Lerner et al (7), showed that toluene treatment induced pore formation in A triplex roots and allowed the leakage of low mol wt substances. Only compounds of mol wt less than that of NAD were able to leak out of roots.…”
Section: Discussionmentioning
confidence: 99%
“…Not only did low mol wt solutes diffuse out of the cells, but other compounds could be introduced into the cells to serve as substrates for in situ enzymic reactions. Lerner et al (7) have applied the toluene treatment method to plant roots. From their experiments they concluded that the size of the pores formed by toluene in Atriplex root cell membranes are smaller than those formed in membranes of microbial or mammalian cells.…”
mentioning
confidence: 99%
“…(Parihar et al, 1994). Interestingly, the embryos treated with toluene, a widely known inducer of transient `pore' formation of specific sizes (Lerner et al, 1978), exhibited significantly higher frequency of GUS expression (78%) at 1:20 v/v dilution with permeabilization buffer (Fig. 1).…”
Section: Influence Of Permeabilizing Agentsmentioning
confidence: 99%